2009
DOI: 10.1002/ejoc.200900589
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Supramolecular Properties of a Novel Octaphosphonate Porphyrin

Abstract: Two complementary routes were developed for preparing novel octaphosphonate porphyrins. The use of protected/deprotected phosphonate-substituted precursors in the rational synthesis gave an overall yield 16 %. A more streamlined synthetic path gave 21 % overall yield of the target molecule. Octaphosphonate porphyrin possesses promising properties in supramolecular aggregate formation with cyclam. Cofacial reversible self-assembly of a meso-substituted octaphos-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, studies along these lines are still limited [ 4 , 5 ]. Nevertheless, in our earlier work, we have demonstrated synthesis of novel octaphosphanatoporphyrin (OctaPhosPor) 1 [ 20 ], and its cofacial reversible self-assembly with cyclam, which yields micrometer long monomolecular nanowires. We speculated that self-assembly was modulated by intermolecular hydrogen bonding of the amino groups of cyclam with phosphonato moieties of 1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies along these lines are still limited [ 4 , 5 ]. Nevertheless, in our earlier work, we have demonstrated synthesis of novel octaphosphanatoporphyrin (OctaPhosPor) 1 [ 20 ], and its cofacial reversible self-assembly with cyclam, which yields micrometer long monomolecular nanowires. We speculated that self-assembly was modulated by intermolecular hydrogen bonding of the amino groups of cyclam with phosphonato moieties of 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of meso-substituted porphyrins was carried out by acid-catalyzed condensation reactions following procedures developed by Lindsey et al , The synthetic route to the porphyrins is shown in Scheme . Compounds 7 , 8 , 9 , 10 , and 11 (Scheme ; Scheme S1, SI) were synthesized by literature procedures. Compound 12 was reported earlier.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of meso-substituted porphyrins was carried out by acid-catalyzed condensation reactions following procedures developed by Lindsey et al 17,18 The synthetic route to the porphyrins is shown in Scheme 1. Compounds 7, 19 8, 20 9, 21 23 5-(Heptafluoropropyl)dipyrrylmethane (12). 2,2,3,3,4,4,4-Heptafluorobutanal (4g, 20.2 mmol) was dissolved in THF (60 mL), and the solution was degassed by argon bubbling for 20 min.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] In recent years, we have undertaken work based on {porphyrin-5,10,15,20-tetrayltetrakis[(benzene-5,1,3-triyl)bis (methylene)]}octakis(phosphonic acid) 1 and reported several findings on nanostructure syntheses using this material such as nanowires, nanorods, spherical aggregates and chiral supramolecular nanostructures using a bottom-up approach based on supramolecular self-assembly. [23][24][25]…”
Section: Introductionmentioning
confidence: 99%